BIAS GENDER DALAM BUKU PENDIDIKAN AGAMA ISLAM SEKOLAH DASAR - Rasyidin, Al (LP2M IAIN Mataram, 2010)
Islam puts men and women in an equal position; what distinguishes them is their degree of pity. However, this egalitarian principle has not always been true in practice. Gender biases can still be found not only in the society in general but also in particular at school and in the textbooks used. This study is aimed to examine critically gender biases in the school textbooks especially on Islamic Religious Education books. The study analyzes four Islamic Education Textbooks published by four different publishers, namely Esis, Yudistira, Tiga Serangkai and Erlangga. The studyâs methodological approach is inquiry qualitative and uses content analysis. The study demonstrates that the textbooks examined echo biases in the form of marginalization, subordination, work burden and stereotyping imposed on a particular gender. Male biases are present in most aspects of the book structure such as in the form of question, expression, narratives and illustration.